(untitled) (International Journal of Engineering and Computer Science, 2024)
Today, the usage areas of polymer materials are quite wide. It is not possible to recycle petroleum-based polymers. Synthetic polymers have wide usage areas; This makes synthetic polymers the most important cause of environmental pollution. In particular, disposable products are produced from synthetic polymer materials and then recycled in nature for many years; It has pushed us to seek a solution to this problem. At the same time, decreasing oil resources pose a raw material threat for the production of oil-based products. Therefore, it is aimed to minimize the use of synthetic polymers used in many industries such as automotive, household appliances, food and pharmaceutical packaging, and to contribute to the increase of biopolymer studies. In this study, the production and mechanical characterization of Polylactic Acid, a natural polymer, was performed. PLA, which is a biodegradable polymer as well as a natural polymer, is thought to be an alternative to synthetic polymers in many sectors. Pure natural PLA samples were molded with an injection device and mechanical characterization was performed. The results of tensile and 3-point bending tests were interpreted. As a result of the mechanical tests of PLA, a biocomposite was produced using chestnut shells to improve the mechanical properties and the mechanical properties of this biocomposite were examined. It was concluded that 25% chestnut shell reinforcement improved the mechanical properties of PLA.